Analysis of the Existence of Size Effect on Different Concrete Types. (2015) - Manić, Nazim; Tarić, Mirsad; Šerifi, Veis; Ristovski, Aleksandar
Abstract: The paper analyzes research on the formula proposed by Bazant, where the existence of size effect is shown. The beams made of different types of concrete loaded at three points, with a slot in the middle of the beam, were experimentally burdened to the point of fracture. The fracture energy (Gf) and the characteristic length in the fracture zone (cf) were determined. For the experiment beams of common, high-quality, lightweight concrete and concrete with steel fibers were used. As the fifth sample ordinary concrete with a change in the width of the bearing under load was made. The maximum size of aggregate grain for the concrete is 10 mm. The beams for the experiment were of three different sizes, and three samples of each size. A total of 45 beams were used. Cross-section of beams was changed proportionally.